A sub-nanometer-thick porous cobalt oxide sheet exposing a specific crystal surface, and a preparation method and application thereof

By hydrothermal reaction in alcohol solution and heating topological conversion, subnano-thick porous cobalt tetraoxide flakes exposed to specific crystal surfaces were prepared, which solved the problems of poor low-temperature activity and high cost of existing catalysts, and achieved efficient low-temperature catalysis and Low cost catalytic effect.

CN116768283BActive Publication Date: 2025-02-18XI AN JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310649668.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-02-18
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

The existing cobalt tetraoxide catalysts have poor catalytic activity at low temperatures, high conversion temperatures, and high cost, which limits their industrial applications.

Method used

Hydrothermal reaction was performed to generate ultrathin CoO sheets with exposed (111) crystal surfaces by adding a cobalt source to the alcohol solution, and sub-nano thickness porous cobalt tetroxide sheets with exposed specific crystal surfaces were obtained by heating topological transformation.

Benefits of technology

It has achieved a high low-temperature catalytic activity, low cost and good water resistance. The degradation rate of propane at 165°C reaches 100%, and its performance is better than other types of Co3O4 catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116768283B_ABST
    Figure CN116768283B_ABST
Patent Text Reader

Abstract

The present invention discloses a sub-nanometer-thick porous cobalt oxide thin sheet with a specific crystal face exposed, a preparation method and an application thereof. A cobalt source is added to an alcohol solution, stirred evenly, and then subjected to a hydrothermal reaction at 190-220°C for 48-96h to obtain an ultra-thin CoO sheet with a (111) crystal face exposed; the ultra-thin CoO sheet with the (111) crystal face exposed is heated. 2 COO ‑ The hydrogen bonds and van der Waals interactions between the species will generate directional short-range attraction between the CoO cores. Driven by the directional short-range attraction and electrostatic interaction, the CoO cores self-assemble into sub-nanometer thick two-dimensional CoO nanosheets with exposed (111) crystal planes. The sub-nanometer thick porous cobalt oxide thin sheets prepared by the present invention have a large number of low-coordinated Co atoms, defect sites and a large reaction area, thereby improving its low-temperature catalytic oxidation activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of air pollution control and technology, and in particular relates to a sub-nanometer-thick porous cobalt oxide sheet exposing a specific crystal plane, a preparation method and an application thereof. Background Art

[0002] As low-carbon alkanes in VOCs, alkane molecules are very stable and difficult to destroy due to their large CH bond energy. Precious metal catalysts are highly active, but they are expensive and prone to sintering and poisoning, which limits their industrial application. Transition metal oxide catalysts have the advantages of good catalytic performance, low cost, and strong anti-poisoning ability, and are considered to be catalysts with great application prospects.

[0003] Chinese patent 201410207035.2 discloses a "cobalt tetraoxide propane complete catalytic oxidant and its preparation method and application". The catalyst is made of Co3O4, but its conversion temperature is still relatively high, T 90 It is 219℃, and the low temperature activity of metal oxides is poor. Summary of the invention

[0004] In order to overcome the problems in the prior art, the purpose of the present invention is to provide a sub-nanometer thick porous cobalt oxide flake exposing a specific crystal plane, a preparation method and an application thereof, which has the characteristics of being economical and cheap, simple in preparation materials, high in low-temperature reaction activity, good in high-temperature stability and good in water resistance.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a sub-nanometer-thick porous cobalt oxide sheet exposing a specific crystal plane comprises the following steps:

[0007] Adding a cobalt source to the alcohol solution, stirring evenly, hydrothermally reacting at 190-220° C. for 48-96 hours, washing, and drying to obtain an ultra-thin CoO sheet with an exposed (111) crystal plane;

[0008] The ultra-thin CoO sheet with exposed (111) crystal plane is heated to obtain a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes.

[0009] Furthermore, the alcohol solution is prepared by adding alcohol or to water, wherein the volume ratio of alcohol to water is 50-200mL:28-40.

[0010] Furthermore, the alcohol is ethylene glycol, propylene glycol or isopropanol.

[0011] Furthermore, the usage ratio of alcohol to cobalt source is 50-200 mL: 200-1000 mg.

[0012] Further, the cobalt source is cobalt 2,4-pentanedioate, cobalt naphthenate or cobalt boroacylate.

[0013] Furthermore, the stirring time is 60-120 min.

[0014] Furthermore, the drying temperature is 60-100° C. and the drying time is 12-24 hours.

[0015] Furthermore, the heating temperature is 300-400° C. and the heating time is 30-60 min.

[0016] A sub-nanometer-thick porous cobalt trioxide sheet with exposed specific crystal planes prepared according to the method described above.

[0017] The invention discloses an application of the sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes in low-temperature catalysis of propane.

[0018] Compared with the prior art, the beneficial results of the present invention are:

[0019] In the present invention, at 190-220°C, ethylene glycol (HOCH2CH2OH) can be partially oxidized to alcohol acid (HOCH2COOH), and CoO nucleates at the same time, and its surface energy can be increased by adsorbing HOCH2COO on its surface. - Due to the ionization of the carboxyl group, HOCH2COO - The presence of HOCH2COO can make the CoO core produce a net negative charge. - The hydrogen bonds and van der Waals interactions between species will generate directional short-range attraction between CoO nuclei. Driven by directional short-range attraction and electrostatic interaction, the CoO nuclei self-assemble into two-dimensional CoO nanosheets with sub-nanometer thickness and exposed (111) crystal planes. The sub-nanometer thickness porous cobalt oxide flakes prepared by the present invention have a large number of low-coordinated Co atoms, defect sites and a large reaction area, thereby improving its low-temperature catalytic oxidation activity. The raw material constituent elements of the present invention are low in price and cost.

[0020] At 20000h -1 Under the condition of an air velocity of 1.5 wt%, the balance gas N2, 21% O2 and 2500 ppm C3H8 are introduced. When the reaction temperature is only 165°C, propane can be completely oxidized. The Co3O4 catalyst prepared by the present invention has good catalytic oxidation performance for propane at low temperature, and the degradation rate of propane at 165°C reaches 100%, and its performance is better than other types of Co3O4 catalysts reported so far. Therefore, the use of the prepared Co3O4 catalyst to catalytically oxidize low-carbon alkanes has certain practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1The electron microscope images of Co3O4-SPS, where (A) is a field emission scanning electron microscope image and (B) is a field emission projection electron microscope image.

[0022] Figure 2 The high-magnification transmission electron microscope images of Co3O4-SPS. (A) is a high-magnification transmission electron microscope image, and (B) is a simulated crystal plane atomic arrangement image.

[0023] Figure 3 The thickness diagram of Co3O4-SPS thin film, where (a) is the atomic force microscope image, (b) is the thickness diagram of the corresponding interval S1, (c) is the thickness diagram of the corresponding interval S2, and (d) is the thickness diagram of the corresponding interval S3.

[0024] Figure 4 The field emission scanning electron micrographs of Co3O4-TS and Co3O4-C are shown in Figure 1. (A) is the field emission scanning electron micrograph of Co3O4-TS, and (B) is the field emission scanning electron micrograph of Co3O4-C.

[0025] Figure 5 The Co3O4 catalyst was in the C3H8 concentration of 2500ppm and the space velocity was 20000h -1 Performance curve of propane catalytic oxidation under test conditions.

[0026] Figure 6 The Co3O4 catalyst was in the C3H8 concentration of 2500ppm and the space velocity was 20000h -1 Graph of CO2 selectivity for propane catalytic oxidation under test conditions.

[0027] Figure 7 For Co3O4-SPS catalyst, the temperature is 165℃, the C3H8 concentration is 2500ppm, and the space velocity is 20000h -1 Long-term stability diagram of propane catalytic oxidation under test conditions.

[0028] Figure 8 For Co3O4-SPS catalyst, the C3H8 concentration is 2500ppm and the space velocity is 20000h -1 Graph of water resistance for catalytic oxidation of propane under test conditions. DETAILED DESCRIPTION

[0029] The present invention is described in detail below with reference to the accompanying drawings.

[0030] The method for preparing a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes of the present invention comprises the following steps:

[0031] First, dissolve 50-200mL of ethylene glycol (or propylene glycol or isopropanol) in 28-40mL of deionized water, then add 200-1000mg of Co(acac)3 (cobalt cyclohexaneate or cobalt boroacylate) and stir for 60-120min. Then transfer the solution to a polytetrafluoroethylene-lined autoclave and heat at 190-220℃ for 48-96h. At 190-220℃, ethylene glycol (HOCH2CH2OH) can be partially oxidized to alcohol acid (HOCH2COOH), and CoO nucleates at the same time, and its surface energy can be increased by adsorbing HOCH2COO on its surface. - Due to the ionization of the carboxyl group, HOCH2COO - The presence of HOCH2COO can make the CoO core produce a net negative charge. - The hydrogen bonds and van der Waals interactions between species will generate directional short-range attraction between CoO cores. Driven by directional short-range attraction and electrostatic interaction, CoO cores self-assemble into sub-nanometer thick two-dimensional CoO nanosheets with exposed (111) crystal planes. After the high-pressure reactor is cooled naturally, the precipitate after the reaction is collected by centrifugation. The collected precipitate is washed 4-8 times with a mixture of water and ethanol in a ratio of 1:9-1:20, and then placed in a vacuum drying oven at 60-100℃ for 12-24h. Then the obtained ultra-thin CoO sheet with exposed (111) crystal plane is finally heated in air at 300-400℃ for 30-60min, and the ultra-thin CoO sheet with exposed (111) crystal plane is topologically transformed to obtain a porous Co3O4 nanosheet with sub-nanometer thickness with exposed (111) crystal plane.

[0032] The present invention investigates the low-temperature catalytic activity of two catalysts, Co3O4 nanosheets with sub-nanometer thickness and traditional bulk Co3O4, and the influence of oxygen on their catalytic activity.

[0033] Catalyst usage: 20000h -1 Under the condition of space velocity, sub-nanometer Co3O4 nanosheets are used as catalysts to catalyze the oxidation of propane in volatile organic matter. The catalytic reaction temperature is 25-500°C, the concentration of propane is 2500ppm, and the volume concentration of oxygen is 21%.

[0034] Example 1

[0035] First, 160 mL of ethylene glycol was dissolved in 30 mL of deionized water, and then 700 mg of Co(acac)3 was added and stirred for 100 min. Then the solution was transferred to a polytetrafluoroethylene-lined autoclave and heated at 200 °C for 60 h. After the autoclave was cooled naturally, the precipitate after the reaction was collected by centrifugation. The collected precipitate was washed 4-8 times with a mixture of water and ethanol in a ratio of 1:9-1:20, and then placed in a vacuum drying oven at 70 °C for 20 h. Then the obtained ultra-thin CoO sheet with exposed (111) crystal plane was finally heated in air at 350 °C for 40 min to obtain a sub-nanometer-thick porous Co3O4 nanosheet, which was crushed and sieved through 40-60 mesh by pressing to obtain a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes, which was recorded as Co3O4-SPS catalyst.

[0036] from Figure 1 Among A and B, Figure 2 A and B and Figure 3 As can be seen from (a)-(d), the catalyst prepared in Example 1 is a porous Co3O4 nanosheet structure with sub-nanometer thickness exposing the (111) crystal plane.

[0037] Example 2

[0038] First, 50 mL of propylene glycol was dissolved in 28 mL of deionized water, and then 200 mg of cobalt cyclohexaneate was added and stirred for 60 min. Then the solution was transferred to a polytetrafluoroethylene-lined autoclave and heated at 220 ° C for 48 h. After the autoclave was cooled naturally, the precipitate after the reaction was collected by centrifugation. The collected precipitate was washed 4-8 times with a mixture of water and ethanol in a ratio of 1:9-1:20, and then placed in a vacuum drying oven at 60 ° C for 24 h. Then the obtained ultra-thin CoO sheet with exposed (111) crystal plane was finally heated in air at 400 ° C for 30 min to obtain a sub-nanometer-thick porous Co3O4 nanosheet, which was crushed and sieved through 40-60 mesh by pressing to obtain a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes.

[0039] Example 3

[0040] First, 100 mL of isopropanol was dissolved in 40 mL of deionized water, and then 1000 mg of cobalt borate was added and stirred for 80 min. Then the solution was transferred to a polytetrafluoroethylene-lined autoclave and heated at 210 ° C for 80 h. After the autoclave was cooled naturally, the precipitate after the reaction was collected by centrifugation. The collected precipitate was washed 4-8 times with a mixture of water and ethanol in a ratio of 1:9-1:20, and then placed in a vacuum drying oven at 80 ° C for 17 h. Then the obtained ultra-thin CoO sheet with exposed (111) crystal plane was finally heated in air at 3000 ° C for 60 min to obtain a sub-nanometer-thick porous Co3O4 nanosheet, which was crushed and sieved through 40-60 mesh by pressing to obtain a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes.

[0041] Example 4

[0042] First, 200 mL of propylene glycol was dissolved in 35 mL of deionized water, and then 500 mg of Co(acac)3 was added and stirred for 120 min. Then the solution was transferred to a polytetrafluoroethylene-lined autoclave and heated at 190 ° C for 96 h. After the autoclave was cooled naturally, the precipitate after the reaction was collected by centrifugation. The collected precipitate was washed 4-8 times with a mixture of water and ethanol in a ratio of 1:9-1:20, and then placed in a vacuum drying oven at 100 ° C for 12 h. Then the obtained ultra-thin CoO sheet with exposed (111) crystal plane was finally heated in air at 320 ° C for 50 min to obtain a sub-nanometer-thick porous Co3O4 nanosheet, which was crushed and sieved through 40-60 mesh by tableting to obtain a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes.

[0043] Comparative Example 1

[0044] 6 mmol Co(OAc)2 was dissolved in 30 mL deionized water under magnetic stirring. After stirring for 15 min, 60 ml 1 g L -1 Carboxymethyl cellulose solution, continue stirring for 30 minutes. Then add 60mL of dilute ammonia water (ammonia water / water = 1 / 9) dropwise to the stirred solution. Subsequently, the solution was transferred to a 250mL polytetrafluoroethylene-lined autoclave, sealed and heated at 80°C for 12 hours. The precipitate at the bottom of the autoclave was collected by centrifugation, washed several times with distilled water and ethanol, and dried in an oven at 100°C. The obtained powder was then directly heated in air at 300°C for 30 minutes, and then cooled to room temperature to obtain flaky Co3O4. It was crushed and sieved through 40-60 mesh by tableting and recorded as Co3O4-TS catalyst.

[0045] from Figure 4 It can be seen from Figure A that the catalyst prepared in Comparative Example 1 is flaky Co3O4.

[0046] Comparative Example 2

[0047] Co(NO3)2·6H2O was heated in a muffle furnace at 900℃ in air for 18h and then cooled to room temperature. The resulting powder was collected and recorded as Co3O4-C.

[0048] from Figure 4 It can be seen from B that the catalyst prepared in Comparative Example 2 is block Co3O4.

[0049] Activity test of the catalysts in Example 1, Comparative Example 1 and Comparative Example 2: 0.15 g of the catalysts obtained in Example 1, Comparative Example 1 and Comparative Example 2 were placed in a fixed bed reactor for catalytic activity evaluation. The experimental conditions were: 2500 ppm C3H8, 21% O2, N2 as the balance gas, and a reaction space velocity of 20000 h -1 The propane concentration was measured by gas chromatography. The catalytic performance results are shown in Figure 5 As shown, from Figure 5 It can be seen that the Co3O4-SPS catalyst can completely oxidize propane at 165 °C, which is much lower than the other two catalysts.

[0050] Example 1, Comparative Example 1 and Comparative Example 2 Catalytic oxidation of propane CO2 selectivity test: 0.15g of the catalysts obtained in Example 1, Comparative Example 1 and Comparative Example 2 were placed in a fixed bed reactor for catalytic activity evaluation. The experimental conditions were: 2500ppm C3H8, 21% O2, N2 as the balance gas, and a reaction space velocity of 20000h -1 . CO2 is detected by gas chromatography. The results of catalyst CO2 selectivity are as follows Figure 6 As shown, from Figure 6 It can be seen that the Co3O4-SPS catalyst can completely oxidize propane to CO2 at 175 °C, which is much lower than the other two catalysts.

[0051] Example 1 Long-term temperature stability test of the catalyst: 0.15 g of the catalyst in Example 1 was placed in a fixed bed reactor for catalytic activity evaluation. The experimental conditions were: 2500 ppm C3H8, 21% O2, N2 as the balance gas, and a reaction space velocity of 20000 h -1 The temperature was controlled at 165°C for 40 hours to test the activity. The propane concentration was detected by gas chromatography. The results of the catalytic high temperature stability performance are as follows: Figure 7 As shown, from Figure 7 It can be seen that the activity of the Co3O4-SPS catalyst remains basically unchanged when kept at 160°C for 40 hours, and it has excellent thermal stability.

[0052] Example 1 Water resistance test of the catalyst: 0.15 g of the catalyst in Example 1 was placed in a fixed bed reactor for catalytic activity evaluation. The experimental conditions were: 2500 ppm C3H8, 21% O2, N2 as the balance gas, and a reaction space velocity of 20000 h -1 The temperature was controlled at 165°C and 160°C for 40 hours to test the activity. During this period, 5% and 10% water were added to the reactor for ten hours, and then the addition of water was stopped. The propane concentration was detected by gas chromatography. The results of the catalyst water resistance are as follows Figure 8 As shown, from Figure 8 It can be seen that the Co3O4-SPS catalyst can still maintain good catalytic activity when 5% and 10% water are added, and has excellent water resistance.

[0053] The low-coordinated metal atoms of the catalyst in catalytic oxidation can serve as highly active sites, which are crucial to the catalytic activity. The sub-nanometer-thick porous cobalt oxide flakes prepared by the present invention have a large number of low-coordinated Co atoms, defect sites and a large reaction area, thereby improving its low-temperature catalytic oxidation activity.

Claims

1. A method for preparing a sub-nanometer-thick porous cobalt oxide sheet exposing a specific crystal plane, characterized in that: The following steps are involved: Adding a cobalt source to the alcohol solution, stirring evenly, and then hydrothermally reacting at 190-220° C. for 48-96 hours, washing, and drying to obtain an ultra-thin CoO sheet with an exposed (111) crystal plane; The ultra-thin CoO sheet with exposed (111) crystal plane is heated to obtain a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes; The cobalt source is cobalt 2,4-pentanedioate, cobalt naphthenate or cobalt boroacylate; The heating temperature is 300-400°C and the heating time is 30-60 minutes.

2. The method for preparing a sub-nanometer-thick porous cobalt oxide sheet exposing a specific crystal plane according to claim 1, characterized in that: The alcohol solution is prepared by adding alcohol into water, wherein the volume ratio of alcohol to water is 50-200 mL:28-40.

3. The method for preparing a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes according to claim 2, characterized in that: The alcohol is ethylene glycol, propylene glycol or isopropyl alcohol.

4. The method for preparing a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes according to claim 1, characterized in that: The usage ratio of alcohol to cobalt source is 50-200mL:200-1000mg.

5. The method for preparing a sub-nanometer-thick porous cobalt oxide sheet exposing a specific crystal plane according to claim 1, characterized in that: The stirring time is 60-120 minutes.

6. The method for preparing a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes according to claim 1, characterized in that: The drying temperature is 60-100°C and the drying time is 12-24h.

7. Use of a sub-nanometer-thick porous cobalt oxide sheet with exposed specific crystal planes prepared by the method according to any one of claims 1 to 6 in low-temperature catalysis of propane.

Citation Information

Patent Citations

  • Propane full-catalytic oxidation agent of cobaltosic oxide as well as preparation method and application of oxidation agent

    CN103990461A